2+1 DIMENSIONAL HOLOGRAPHIC SUPERCONDUCTOR EINSTEIN-MAXWELL-COMPLEX SCALAR SYSTEM IN PROBE LIMIT - Al-Asy'Ari, Hasan
A most remarkable result to emerge from string theory is AdS/CFT duality, which relates string theory on asymptotically anti-de Sitter spacetime to a conformal field theory on the boundary. This conjecture is also often called holographic theory. One application of this conjecture is in superconductivity phenomena. Macroscopically, superconductivity can be explained by GL (Ginzburg-Landau) theory. While microscopically it is explained by BCS (Bardeen, Cooper, Schrieffer) theory. However, there are some things that can not be explained by these two theories. One of them is high Tc superconductors. AdS/CFT Duality conjecture is expected to provide an explanation of high Tc superconductors. In this final project, basic concepts of AdS/CFT duality and some physics phenomena which are the basis to learn and research about holographic superconductors will be reviewed. In outline, the material reviewed is taken from lecture notes of Makoto Natsuume titled AdS/CFT Duality User Guide. Here, writer tries to exemplify two superconductivity phenomena that can be described by a gravitational theory, namely critical phenomena and electrical conductivity. The system to be considered is Einstein-Maxwell-complex scalar in probe limit.